Efektivitas Singkong Mentah (Manihot Esculenta) Sebagai Rodentisida Nabati Terhadap Pengendalian Tikus Mencit (Mus Musculus) - Ayu Noer Fazriyawati; Hardiono Hardiono; Rahmawati Rahmawati (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
The Effectiveness Of Raw Cassava As A Vegetable Rodenticide (Manihot esculenta) To Control The Mice(Mus musculus). Mice are rodents that cause economic losses and disease carriers for humans. Control is often done by using rodenticide containing toxic chemicals, but its use is not enviromentally responsible way. As an alternative to rodenticide then using vegetable rodenticide made from natural material, one of which cassava contain cyanide acid. This compound is dangerous, if consumed will be quickly absorbed by the digestive tract and into the bloodstream, can cause pain and even cause death. This study aimed to find out LD50 raw cassava against white mice death. This type of research was an experiment with Post-test Only Control Group Design. The sample used were 50 male white mice of the Mus musculus species with the amount of rodenticide treatment of 40 gram, 60 gram, 80 gram and 100 gram. The results obtained the highest mortality mortality of 60% at a dose of 100 gra with a consumption rate of 62,48 gram. Calculation results LD50 with probit analysis method obtained LD50 value of 62,48 gram, so the conclusion is 61,60g doses of cassava is capable of using the death of 50% mice.